Adaptive Transmission Range Based on Event Detection for WSNs - Autanan Wannachai (2018)
© 2015 IEEE. Wireless sensor networks usually pay attention to energy efficiency by reducing the data transmission rate or using data aggregation techniques. However, in an urgent situation of a disaster monitoring application, sensing data become very important. The sensing data are required to be at the base station quickly so that the administrators can evaluate the situation and issue the early warning message. This paper focuses on the adaptive operations of sensor nodes. The sensor nodes can automatically adjust its transmission range based on the degree of importance of sensing data. In the urgent situation, the transmission range is increased to reduce the number of hops to reduce the latency. In the normal situation, the transmission range is decreased to reduce the battery consumption of sensor nodes. The proposed mechanism, called A-TRED, evaluates the degree of importance of sensing data and adjusts the transmission range of sensor nodes accordingly. A-TRED consists of three processes which are 1) data checking process, 2) packet formation process, and 3) packet forwarding process. The simulation results show that A-TRED can automatically adapt WSN key performance factors (e.g., latency, battery consumption) by adjusting the transmission range against the environmental changes.